Creating Green Circular Economy in Waste Management: The Kampung Hijau Bank Sampah Al-Haqiqi Case - Hidayatullah, Muhammad Rizqi; Fadhliana, Dian (Global Writing Academica Researching and Publishing, 2023)
The concept of the circular green economy strives to address the issue of waste generated by society, aiming to prevent it from becoming a more complex environmental problem. This study aimed to comprehensively analyze the efforts of PT Pertamina Patra Niaga DPPU Bandara Internasional Lombok through the CSR program “Kampung Hijau Bank Sampah Al-Haqiqi” in changing the community’s paradigm in waste management. This study employed a qualitative method with a case study approach. The data used in this research included primary data collected through observations and interviews with beneficiaries. Secondary data were gathered from program implementation reports, monitoring and evaluation reports, and supplemented with relevant journal articles. This study reveals that 1) The CSR program of Al-Haqiqi Waste Bank adopts a new paradigm for waste management and assists in changing community habits regarding household waste management 2) Kampung Hijau Bank Sampah Al-Haqiqi program encourages the emergence of the circular economy, leading to not only environmental sustainability but also economic improvement 3) Kampung Hijau Bank Sampah Al-Haqiqi program accelerates the achievement of development goals, particularly focusing on SDG Goal 12 and the reduction of GHG emissions, amounting to 893 kg of CH4 and 17,860 kg of CO2.